DESIGN OF SOIL IMPROVEMENT AND PUSH-IN PILE FOUNDATION OF A STADION IN GEDEBAGE, BANDUNG - Setiawan Susilo Juwono, Yosafat
Geotechnical works in this stadion consist of deep foundation engineering and improvement of a soil layer near the surface. The purpose of Soil Improvement in the Stadion Construction Project in Gedebage Region, Bandung is to strengthen the base soil layer of the parking lot, the stadion’s construction area, and the the road which encircles the stadion building. For this purpose, the soil improvement forementioned has to be able to increase the California Bearing Ratio (CBR) of the top layer of the soil (from 0-4 meter below the ground surface) to above 6% in the shortest possible duration. To achieve this, application of preloading and Prefabricated Vertical Drain (PVD) is needed. Preloading is applied in the form of gravel embankment 7 meters in height and slope with a gradient of 1:2. The slope’s global stability (during construction of embankment, after the construction, and during the removal stage) is calculated using PLAXIS software. Preloading will increase the strength of the soil (Strength gain) by applying and consolidating in the site. The PVDs that will be used are PVD VD808 with equivalent drainage diameter of 66.21 mm (thickness of 4 and length of 100 mm) that are placed in triangular configurations with each PVD spaced 1000 mm from the other. PVD will be applied to decrease the time needed for 90% consolidation during the application of the preload. Preloading weight for this project is in a form of dense sand with 21 kN/m3 of density 3.2 meters in height for the stadion construction area, and 3.28 meters for the parking lot construction area. Deep foundation is needed in this project because of the existence of soft or very soft clay down to the depth of 20-30 meter below ground surface. The chosen type of foundation is Push-in Pile Precast foundation that is easy to install and at the same time does not produce loud sounds that could disturb the neighborhood. The chosen pile’s specification is in accordance with the type C Precast SpunPile from PT Wijaya Karya Beton, tbk, with a diameter of 0.8 meter for small groups of pile iv (P1, P2, P4, P6, P9) and 1.0 meter for larger group of piles (P24, P25, P56, P63) and is applied to soil 32 meters below ground surface.